Heterogeneity in the association between weather and pain severity among patients with chronic pain: a Bayesian multilevel regression analysis. (12th January 2022) - Yimer, Belay B.; Schultz, David M.; Beukenhorst, Anna L.; Lunt, Mark; Pisaniello, Huai L.; House, Thomas; Sergeant, Jamie C.; McBeth, John; Dixon, William G.
Abstract : Supplemental Digital Content is Available in the Text. Weather sensitivity among patients with chronic pain is a phenomenon more apparent in some participant subgroups. Abstract: Introduction: Previous studies on the association between weather and pain severity among patients with chronic pain have produced mixed results. In part, this inconsistency may be due to differences in individual pain responses to the weather. Methods: To test the hypothesis that there might be subgroups of participants with different pain responses to different weather conditions, we examined data from a longitudinal smartphone-based study, Cloudy with a Chance of Pain, conducted between January 2016 and April 2017. The study recruited more than 13, 000 participants and recorded daily pain severity on a 5-point scale (range: no pain to very severe pain) along with hourly local weather data for up to 15 months. We used a Bayesian multilevel model to examine the weather–pain association. Results: We found 1 in 10 patients with chronic pain were sensitive to the temperature, 1 in 25 to relative humidity, 1 in 50 to pressure, and 3 in 100 to wind speed, after adjusting for age, sex, belief in the weather–pain association, mood, and activity level. The direction of the weather–pain association differed between people. Although participants seem to be differentially sensitive to weather conditions, there is no definite indication that participants' underlying pain conditions play a role in weather sensitivity. Conclusion: This study demonstrated that weather sensitivity among patients with chronic pain is more apparent in some subgroups of participants. In addition, among those sensitive to the weather, the direction of the weather–pain association can differ.